2014
DOI: 10.1098/rspa.2013.0547
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of chirality-induced bi-directional swimming of artificial flagella

Abstract: Biomimetic micro-swimmers can be used for various medical applications, such as targeted drug delivery and micro-object (e.g. biological cells) manipulation, in lab-on-a-chip devices. Bacteria swim using a bundle of flagella (flexible hair-like structures) that form a rotating cork-screw of chiral shape. To mimic bacterial swimming, we employ a computational approach to design a bacterial (chirality-induced) swimmer whose chiral shape and rotational velocity can be controlled by an external magnetic field. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…To model the robot locomotion and fluid flow created by the robot, we used a computational fluid dynamics (CFD) model ( 59 , 60 ), which could accurately describe the robot motion and the deformation-induced fluid flow at low Re . In the CFD model, the midplane of the robot was meshed by shell elements.…”
Section: Methodsmentioning
confidence: 99%
“…To model the robot locomotion and fluid flow created by the robot, we used a computational fluid dynamics (CFD) model ( 59 , 60 ), which could accurately describe the robot motion and the deformation-induced fluid flow at low Re . In the CFD model, the midplane of the robot was meshed by shell elements.…”
Section: Methodsmentioning
confidence: 99%
“…Movie 3 for a long run of a zoospore swimming in water). It has been shown that microswimmers with chiral shape of the body and asymmetric arrangement of their flagella are among the reasons causing this self rotational motion [26, 36, 37]. By quantifying the pitch of the helical trajectories, we achieve the rotational speed of the cell body approximately 3.5 π rad s −1 .…”
Section: Role Of Two Flagella Cooperation In Swimming Motions Of Zoosporesmentioning
confidence: 95%
“…For example, a fully coupled implicit solver for the interaction of slender flexible shells and Stokes flow is presented in [17] where geometrically nonlinear elastic structural response is resolved by FEM, and BEM is used for the Stokes flow. The resulting framework has been successfully used to analyze artificial cilia and to investigate swimming direction control strategies, see [18]. However, a simpler, solely finite element-based approach would be a valuable tool to address similar problems within shorter computational times.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the author's knowledge, the treatment of thin shell-type flexible bodies in combination with the resistive force theory has not been addressed fully yet. The only work in this context was presented in the appendix of reference [18] in which an RFT-based analysis of a slender flexible shell was carried out. However, in this analysis, the elastic forces developing in the slender deformable body were not taken into account, and in that sense it was incomplete.…”
Section: Introductionmentioning
confidence: 99%